EXPLORING THE DYNAMICS DURING COMMUNITY ASSEMBLY THROUGH COMMUNITY PHYLOGENETICS - Rena Tri Hernawati; Daisy Wowor; Nicolas Hubert (Treubia, 2015)
Species diversify through speciation and accumulate in ecological community, a process known as community assembly. Relying on both evolutionary mechanisms acting at regional scale and ecological mechanisms acting at local scale, the process of community assembly results from intricate interactions among mechanisms at play across varying spatial and temporal scales. During the last decade, community assembly theory has been reconsidered in the light of evolutionary dynamics of species diversification and ecological dynamics have been formalized in an explicit spatial framework (i.e. metacommunity theory). The aims of the present review are: (1) to present the community assembly theory and the main paradigms that have been proposed, (2) to discuss how the metacommunity theory as defined an explicit spatial framework for community ecology, (3)to discuss the potential mechanisms at play during community assembly and their associated predictions, (4) to present new approaches to study community assembly based on phylogenetics approaches and discuss how they have been integrated in empirical studies.